Benefits of Endoscopic Sheath in Intraventricular Neuroendoscopy: Technical Note - Marx, Sascha; Schroeder, Henry W.S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background The usefulness of the endoscopic sheath is underreported in the literature.Objective and Methods To explain the use of an endoscopic sheath and to highlight its benefits.Results In addition to protecting the surrounding brain parenchyma when inserting the endoscope, the endoscopic sheath is a very useful tool to retract neurovascular structures, achieve hemostasis, and create adequate working space within narrow ventricles. The sheath can be moved within the ventricular system, and the endoscope can be moved independently within the sheath. These movements represent all the advantages of the endoscopic sheath.Conclusions We used an endoscopic sheath in ∼ 300 intraventricular neuroendoscopic procedures and consider the sheath an essential part of a ventriculoscopic system. Proper use of the sheath can help avoid or manage endoscopic complications.
Keywords: endoscopic sheath; neuroendoscopy; tissue retraction